HUBUNGAN PENGETAHUAN, JUMLAH ANAK DAN UMUR DENGAN PENGGUNAAN KONTRASEPSI SUNTIK - Susmini, Susmini (JURNAL MEDIA KESEHATAN, 2018)
KB formulated as an effort to increase awareness and public participation under the age limit of marriage, birth control, fostering family resilience, improving the welfare of the family to realize a small family happy and prosperous (BKKBN, 2011). The purpose of this study to determine the relationship of Knowledge, Number of Children (Parity) and Age With Injectable Contraceptive Use In Puskesmas Megang District of North Lubuklinggau II Lubuklinggau 2014. This study used a survey method with cross sectional Analytical. With a total population of 325 people. Sampling by means of random sampling. The respondents are all over acceptors in Puskesmas Megang District of North Lubuklinggau II Lubuklinggau 2014 totaling 65 people. From the research of 65 respondents obtained knowledge with the use of injectable contraceptives, respondents Knowledge obtained the highest results were knowledgeable enough respondents was 25 (38.5%) of respondents. From the research of 65 respondents Number of respondents children obtained the highest results that respondents with the number of children a little ? 2 there were 33 (50.8%) of respondents who use injectable contraceptives. From the research of 65 respondents to the Age of respondents obtained the highest results were age with low risk (age 20-35 years) amounted to 49 (75.4%) of respondents who use injectable contraceptives. From the results of bivariate analysis showed no significant relationship between knowledge and injectable contraceptives p value = 0.131, the results of the bivariate also showed no significant relationship between the number of children with CICs p value = 0.329 and the results of the bivariate also showed a significant relationship between age CICs with p value = 0,040. Results of this research are expected to be a driving force for health workers, especially Puskesmas Megang District of North Lubuklinggau II Lubuklinggau to provide education on contraception mamfaat to adjust the spacing births.